Vizualno razvrščanje konstrukcijskega žaganega lesa - Šega, Bogdan (Les (Ljubljana), 2010)
Sawn timber used in load-bearing building structures shall comply with the requirements given in harmonized European standard SIST EN 14081-1. Timber shall be either visually or machine graded. Machine grading is based on non-destructive testing (NDT) methods. Considering so called grade indicating properties measurements, timber pieces are graded into previously defined strength classes. Through visual grading each piece of timber is evaluated based on visual parameters. Visual grading rules consider the conformance of surface strength reducing, geometrical and biological characteristics to limitations established within each grade category. On that basis, so called visual strength grades (Sortierklassen) are assigned. Considering visual strength grades, species and sources of timber, strength classes can be assigned according to SIST EN 1912.
Keywords: žagan les; vizualna kontrola; razvrščanje